Performance of tree stand growth and nutrient status of a reclaimed land - Abugre, S.; Adusu, D; Ampofo, K. T. (International Journal of Agricultural Technology, 2019)
The evaluation of tree growth performance and their corresponding effect on soil nutrient status is very crucial in selection of suitable species for reclamation and revegetation of degraded lands for their prompt recovery. This study was therefore evaluated the growth performance and nutrient status of a 30.4 hectares’ land reforested by Newmont Ghana Gold Limited in 2002. Five 50 x 50 m plots were conducted in pure stands of Senna siamea, Tectona grandis, Cedrela odorata and mixed stand with an adjacent control plot. The 50 x 50 m plots were then divided into twenty-five (25) 10 x 10 m subplots from which five were randomly selected under each stand for growth performance and soil nutrient status assessment. The results showed significant differences in all growth and soil parameters measured among the stands. Among all the growth parameters measured Cedrela odorata stand generally recorded the highest growth followed by the mixed, Senna siamea and Tectona grandis stands respectively. The Cedrela odorata stand recorded a mean height of 17.29 m followed by 13.16 m, 12.89 m and 12.32 m for the Senna siamea, mixed and Tectona grandis stands respectively. Mean diameter values of 24.35 cm, 19.43 cm, 17.57 cm and 16.03 cm were recorded in Cedrela odorata, mixed, Senna siamea and Tectona grandis stands respectively. The highest levels of soil macro nutrient, pH (6.21), organic matter (6.05 %) and organic carbon (3.51 %) content were generally recorded under the Cedrela odorata stand. Generally, Cedrela odorata proved to be very useful tree species for reclamation of degraded lands.